Model Perencanaan dan Pengadaan Obat dengan Metode ABC Indeks Kritis (Studi Kasus Di Rumah Sakit Jiwa dr. Soeharto Heerdjan Jakarta) - Yune Laukati; Rina Mutiara; Nofi Erni (Jurnal Health Sains, 2022)
The drug planning and procurement system is a determining factor for drug availability and budget requirements. A good method can be applied to create a good drug planning and procurement system, one of which is the ABC Critical Index method. With this method, priority drugs can be grouped that have a large investment value. RSJ dr. Suharto Heerdjan has never done an ABC Critical Index analysis and the problem that often occurs is the stock of drugs is empty. Suharto Heerdjan Jakarta. This type of research is descriptive qualitative, using data on drug use for the period January 2020 to June 2021 and filling out the VEN questionnaire by 15 doctors. The analysis was carried out using the ABC Critical Index method. The results of the analysis showed that of the 351 types of drugs that were included in group A, there were 6 types of critical index (2%), group B had 119 types of critical index (33.6%) and group C had a critical index of 119 types (33.6%). 226 species (64.4%). Drugs included in group A of the critical index are psychotropic drugs, namely Clozapine 100 mg, Clozapine 25 mg, Trihexyphenidil 2 mg, Risperidone 2 mg, Depakote 500 mg ER, Abilify 10 mg Discmelt. Group A critical index drugs are a priority to be planned and procured, so for the six types of drugs, the estimated demand for 2022, EOQ, SS and ROP are calculated with the following results: Clozapine 100 mg needs 194,844 tablets, EOQ 5,401 tablets, SS 16,953 tablets, ROP 17,654 tablets; Clozapine 25 mg needs 407,080 tablets, EOQ 21,338 tablets, SS 25,892 tablets, ROP 27,194 tablets; Trihexyphenidil 2 mg needs 1,695,404 tablets, EOQ 93,399 tablets, SS 29,544 tablets, ROP 33,387 tablets; Risperidone 2 mg needs 1,073,301 tablets, EOQ 42,897 tablets, SS 12,963 tablets, ROP 14,967 tablets; Depakote 500 mg ER needs 107,971 tablets, EOQ 3,068 tablets, SS 1,980 tablets, ROP 2,110 tablets; Abilify 10 mg discmelt needs 99,737 tablets, EOQ 1,426 tablets, SS 587 tablets, ROP 680 tablets. The application of the drug planning and procurement model using the ABC Critical Index method in research can help determine drug priorities, adjust to budget availability without disrupting the smooth running of services, and improve drug use efficiency